Influence of Concrete-Pictorial-Abstract (CPA) Approach on the Enhancement of Primary School Students’ Mathematical Reasoning Ability - Putri, Hafiziani Eka; Suwangsih, Erna; Rahayu, Puji; Nikawanti, Gia; Enzelina, Elfriyani; Wahyudy, Mukhamad Ady (Mimbar Sekolah Dasar, 2020)
This research is motivated by the importance of mathematical reasoning abilities for primary school students. This research aims at looking at the effect of the Concrete-Pictorial-Abstract (CPA) approach on the enhancement of mathematical reasoning abilities of primary school students. This research method is a quasi-experiment with pre-test and post-test control group design in Mathematics subjects with the theme of data presentation. The research sample consisted of 121 fifth grade students in two primary schools in Bekasi Regency. The test and non-test instruments were involved in this research. The results revealed that there wasthe influence between the CPA approach and students' mathematical reasoning abilities, and the achievement and enhancement of mathematical reasoning abilities of students who got learning with the CPA approach werebetter than students who got conventional learning based on all student review and a category of Prior Mathematical Ability (PMA) high, moderate and low. In conclusion, the mathematical reasoning ability of primary school students can be improved by applying the CPA approach.